Introverted Students’ Perceptions of the Yoodli AI in Public Speaking Course - halim, rossy (Faculty of Language and Literature, University of Surakarta, 2024)
This research evaluates the impact of the developed artificial intelligence tool- Yoodli on public speaking skills as well as the confidence of introverted students. AI technology has grown rapidly in education, but little research focuses on its impact on introverted users. Qualitative methods are used, with data collection through observation and in-depth interviews. The results of the study showed that the majority of participants experienced significant improvements in public speaking skills and confidence after using Yoodli. These results show that Yoodli can be a useful solution for resolving introverts' difficulties when giving public speeches. Moreover, Yoodli may be customized to satisfy various individual demands and offer objective, consistent feedback. The research enriched the literature on learning public speaking skills by adding new perspectives on the use of AI.